2013
DOI: 10.1016/j.tplants.2013.07.006
|View full text |Cite
|
Sign up to set email alerts
|

Trans-acting small interfering RNA4: key to nutraceutical synthesis in grape development?

Abstract: The facility and versatility of microRNAs (miRNAs) to evolve and change likely underlies how they have become dominant constituents of eukaryotic genomes. In this opinion article I propose that trans-acting small interfering RNA gene 4 (TAS4) evolution may be important for biosynthesis of polyphenolics, arbuscular symbiosis, and bacterial pathogen etiologies. Expression-based and phylogenetic evidence shows that TAS4 targets two novel grape (Vitis vinifera L.) MYB transcription factors (VvMYBA6, VvMYBA7) that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
47
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(53 citation statements)
references
References 155 publications
5
47
0
Order By: Relevance
“…When the phased regions were examined using the NCBI BLAST database the majority of these aligned against disease-responsive genes, particularly genes belonging to protein families with nucleotide binding site leucine-rich repeats (NB-LRR) domains. The production of phasiRNAs was demonstrated earlier for NB-LRR protein families [20], [50], [53][55], as well as for pentatricopeptide repeat (PPR) [50], [52], [53], [56], MYB [5], [57], [58] and Auxin Signalling F-Box (AFB) protein families [5], [50]. All of these protein families also displayed phasiRNA generation in this study.…”
Section: Resultssupporting
confidence: 67%
“…When the phased regions were examined using the NCBI BLAST database the majority of these aligned against disease-responsive genes, particularly genes belonging to protein families with nucleotide binding site leucine-rich repeats (NB-LRR) domains. The production of phasiRNAs was demonstrated earlier for NB-LRR protein families [20], [50], [53][55], as well as for pentatricopeptide repeat (PPR) [50], [52], [53], [56], MYB [5], [57], [58] and Auxin Signalling F-Box (AFB) protein families [5], [50]. All of these protein families also displayed phasiRNA generation in this study.…”
Section: Resultssupporting
confidence: 67%
“…These siRNAs, called trans -acting siRNAs or ta-siRNAs, are produced by DCL4 from dsDNA that is generated by the action of Suppressor of Gene Silencing 3 (SGS3) on the miRNA-cleaved TAS transcript following its transcription by RNA-dependent RNA polymerase 6 (RDR6) (Liu et al 2014; Rock 2013). The miRNA-mediated cleavage of the TAS gene transcript sets the registration point for phasing.…”
Section: Mirna and Stress Regulation Mechanismsmentioning
confidence: 99%
“…The fundamental question arises about whether only cis-acting elements present in the promoters of these MYBs are responsible for differential expression or whether any other trans-factors also determine their regulatory mechanisms. Numerous past studies have suggested that miR858 can target R2R3-MYBs in apple, grape, and S. miltiorrhiza (Xia et al, 2012;Rock, 2013;Li et al, 2014). In a quest for such factors, we have shown that miR858a controls the expression of flavonol-specific MYBs, such as MYB11, MYB12, and MYB111 in addition to other members of the MYB family, and studied its detailed role further in Arabidopsis.…”
mentioning
confidence: 91%
“…(Lu et al, 2013;Wang et al, 2014). It has been reported that the miR159, miR319, and miR828 families deregulate MYB transcription factors in apple (Malus domestica), tomato (Solanum lycopersicum), grape (Vitis vinifera), and Salvia miltiorrhiza (Xia et al, 2012;Rock, 2013;Li et al, 2014;Jia et al, 2015). Similarly, a study demonstrated that miR828 regulates MYB2, which is involved in Arabidopsis trichome and cotton (Gossypium hirsutum) fiber development (Guan et al, 2014).…”
mentioning
confidence: 99%